Angelica keiskei Impacts the Lifespan and Healthspan of Drosophila melanogaster in a Sex and Strain-Dependent Manner - Mahtab Jafari; Samuel E. Schriner; Yun-Seo Kil; Sally T. Pham; Eun Kyoung Seo (MDPI AG, 2023)
Angelica keiskei is a perennial plant, belonging to the Apiaceae family and originating from Japan. This plant has been reported to act as a diuretic, analeptic, antidiabetic, hypertensive, tumor, galactagogue, and laxative. The mechanism of action of A. keiskei is not known, but previous studies have suggested that it may act as an antioxidant. In this work, we used Drosophila melanogaster to evaluate the impact of A. keiskei on lifespan and healthspan and its potential anti-aging mechanism by conducting multiple assays on three fly strains: w1118, chico, and JIV. We observed that the extract extended lifespan and improved healthspan in a sex- and strain-dependent manner. A. keiskei extended lifespan and improved reproductive fitness in female flies and either had no effect or decreased survival and physical performance in males. The extract protected against the superoxide generator paraquat in both sexes. These sex-specific effects suggest that A. keiskei may act through age-specific pathways such as the insulin and insulin-like growth factor signaling (IIS) pathways. Upon examination, we found that the increased survival of A. keiskei-fed females was dependent on the presence of the insulin receptor substrate chico, supporting the role of IIS in the action of A. keiskei.